The Influence of Business Capital and Owner's Personality on Small & Medium-Sized Enterprises (SMEs) Development - Sudja’i Sudja’i; Ernawati Ernawati (metromedia.education, 2021)
SMEs are one of the contributors to increasing the national economy. SMEs themselves are able to have a good impact on the environment around SMEs. SMEs create job opportunities for local residents. The problem that often occurs in SMEs in Indonesia is the difficulty of SMEs to get business capital and how the personality of the business owner is. This quantitative research was conducted on SMEs in Kediri, East Java. Sampling was done by random sampling. The sample used was 46 respondents. This research uses multiple linear regression data analysis techniques. Business capital has a significant effect on the development of SMEs. The personality of the SMEs owner has a significant influence on the development of SMEs. Business capital and the personality of the SMEs owner have a significant effect on the joint development of SMEs.